A manual for practical classes on course "Quality management" - Prokhorenko, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2024)
The course “Quality management” is aimed at mastering the approaches and methods of quality management as well as methods and tools used in the planning, design, implementation and development of quality management systems (QMS) in accordance with the requirements of international standards ISO 9001 series. The goal of the course is to provide students with theoretical knowledge and practical skills in the application of general principles, approaches and methods of projection, development, implemen tation, certification and continuous improvement of QMS in accordance with the provisions of ISO 9001 series. The course conventionally consists of two parts. The first part is an overview of the evolution and modern approaches to quality management. The second part has a practical focus and introduces the ISO series of quality management standards, as well as aims to acquire practical skills in building a quality system at an enterprise in accordance with the requirements of the ISO 9001:2015 standard.
Keywords: manual; quality management; quality management systems; methods of projection; certification; management